Aggregation-induced emission organogel formed by both sonication and thermal processing based on tetraphenylethylene and cholesterol derivative. (June 2019) - Luo, Miao; Wang, Sheng; Li, Chengpeng; Miao, Wangen; Ma, Xiang
Abstract: In this work, we designed and synthesized a novel asymmetric tetraphenylethylene-based fluorescence compound, which can form cholesteryl liquid crystal by cooling from the isotropic melt and exhibit typical AIE property with a 180-fold enhancement of fluorescence intensity in 90% water fraction of THF/water mixture than pure THF. This compound can gelate in cyclohexane via both ultrasound stimuli and general sol–gel processes accompanied by remarkable enhanced fluorescence emission. The self-assembly and gelling properties can be controlled by ultrasound stimuli and renewed by a thermodynamic process. The mechanism of the process was investigated by UV–Vis absorption, PL emission, scanning electron microscopy, wide-angle X-ray scattering analysis, and small-angle X-ray scattering analysis. The results reveal that the cooperation and relative competition of multiple intermolecular interactions, which are the main contributors for the formation of gel influenced by the sonication or thermal stimulus. Graphical abstract: Image 1 Highlights: A novel asymmetric tetraphenylethylene-based compound was synthesized. The compound can form cholesteryl liquid crystal and exhibit enhanced emission via both ultrasound and thermal stimuli.